Association of Beta Blocker Use With Bone Mineral Density in the Framingham Osteoporosis Study: A Cross‐Sectional Study. (30th July 2020) - Lary, Christine W; Hinton, Alexandra C; Nevola, Kathleen T; Shireman, Theresa I; Motyl, Katherine J; Houseknecht, Karen L; Lucas, F. Lee; Hallen, Sarah; Zullo, Andrew R; Berry, Sarah D; Kiel, Douglas P
ABSTRACT: Some, but not all, prior observational studies have shown that beta blocker (BB) use is associated with lower fracture risk and higher bone mineral density (BMD). Rodent studies show the mechanism to involve the reduction in the effects of beta‐adrenergic signaling on bone remodeling. Because previous studies did not have detailed information on dose, duration, and beta‐1 selectivity, we examined these in a cross‐sectional analysis of the association between BB use and hip and spine BMD using DXA with the Offspring Cohort of the Framingham Heart Study. The sample size was n = 1520, and 397 individuals used BBs. We used propensity score modeling to balance a comprehensive set of covariates using inverse probability of treatment weighting (IPTW) to minimize bias due to treatment indication. We found significant differences in BMD between BB users and non‐users for three of four BMD measurements (femoral neck: 3.1%, 95% CI, 1.1% to 5.0%; total femur: 2.9%, 95% CI, 0.9% to 4.9%; femoral trochanter: 2.4%, 95% CI, −0.1% to 5.0%; and lumbar spine: 2.7%, 95% CI, 0.2% to 5.0%). Results were found to be similar between sexes although the magnitude of association was larger for women. Similar differences were estimated for beta‐1 selective and nonselective BBs compared with no BB use. We modeled dose in categories (no BB use, low‐dose, high‐dose) and as a continuous variable and found an increasing dose response that levels off at higher doses. Finally, associations were similar for short‐term versus long‐term (≤4 years versus >4 years) use. In summary, this large comprehensive study shows that BB use is associated with higher BMD in a dose‐related manner regardless of beta‐1 specificity and duration of use, which supports the conduct of a randomized clinical trial of BBs for achieving improvements in BMD for individuals at risk of bone loss with aging. © 2020 The Authors. JBMR Plus published by Wiley Periodicals LLC. on behalf of American Society for Bone and Mineral Research. Abstract : Predicted bone mineral density (BMD) in g/cm 2 as a function of standardized dose (defined daily dose [DDD]) in polynomial dose response models with sample weighing by inverse probability of treatment weights (IPTW).